Factors Related to the Complaints of Musculoskeletal Disorders of Shelving Staff - Yovian Treesyanova (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: Every worker is exposed to the risk of occupational accidents or occupational diseases when working. Awkward working postures are the postures that cause body parts to detach from its natural postures that can result in the complaints of musculoskeletal disorders (MSDs). This research intends to analyze the factors related to the complaints of MSDs suffered by the shelving staff in the library and reading room in Universitas Airlangga Surabaya. Methods: This research is observational research that applies a cross-sectional design. The sample of this research consists of 27 people chosen by the total population method. The data regarding the individual characteristics and the complaints of MSDs are obtained through interview and filling out a questionnaire that has been standardized. The data on working postures are analyzed by referring to the Rapid Entire Body Assessment (REBA) method, while the data on the complaints of MSDs are scrutinized by implementing the Nordic Body Map (NBM) method. Results: Reveal that most of the shelving staff experience very high-risk level of MSDs (40.7%). Other than that, it is noticed that the working postures consist of squatting (high-risk level), bowing (high-risk level), standing (moderate-risk level), standing with arms stretching (very high-risk level), and standing with arms stretching while tiptoeing (very high-risk level). The collected data is analyzed by using the Spearman correlation test. Conclusion: It can be stated that the strongest factor causing the occurrence of MSDs is the years of service (r=0.803) with a positive relationship, which means that the longer the years of service is, the higher the risk to experience MSDs is. Keywords: complaints of musculoskeletal disorders, individual factors, shelving staff